CyClick Chemistry for the Synthesis of Cyclic Peptides. (7th November 2019) - Adebomi, Victor; Cohen, Ryan D.; Wills, Rachel; Chavers, Holland Andrew Hays; Martin, Gary E.; Raj, Monika
Abstract: Here, we report a novel "CyClick" strategy for the macrocyclization of peptides that works in an exclusively intramolecular fashion thereby precluding the formation of dimers and oligomers via intermolecular reactions. The CyClick chemistry is highly chemoselective for the N‐terminus of the peptide with a C‐terminal aldehyde. In this protocol, the peptide conformation internally directs activation of the backbone amide bond and thereby facilitates formation of a stable 4‐imidazolidinone‐fused cyclic peptide with high diastereoselectivity (>99 %). This method is tolerant to a variety of peptide aldehydes and has been applied for the synthesis of 12‐ to 23‐membered rings with varying amino acid compositions in one pot under mild reaction conditions. The reaction generated peptide macrocycles featuring a 4‐imidazolidinone in their scaffolds, which acts as an endocyclic control element that promotes intramolecular hydrogen bonding and leads to macrocycles with conformationally rigid turn structures. Abstract : Ausschließlich intramolekular : Die konformativ induzierte Aktivierung der Amidbindung, die Idee hinter der „CyClick"‐Strategie, wird für die Makrozyklisierung von Peptiden genutzt und schließt die Bildung von Dimeren oder Oligomeren durch intermolekulare Reaktionen aus. Diese Methode ist verträglich mit einer Vielzahl von Peptidaldehyden und wurde für die Synthese von 12‐ bis 23‐gliedrigen Ringen eingesetzt.